Examining the Impact of Medical Records towards Services Delivery in Referral Hospitals; A Case Study of Kambuga Referral Hospital, Kanungu District. - Scovia, Tumwakire (Kabale University, 2019)
A Research Report Submitted to the Faculty of Arts and Social Sciences in Partial Fulfillment of the Requirements for the Award of Diploma in Records Management of Kabale University.